A Single Nucleotide Polymorphism in the Vitamin D Receptor Gene Is Associated With Decreased Levels of the Protein and a Penetrating Pattern in Crohn's Disease - Gisbert-Ferrándiz, Laura; Salvador, Pedro; Ortiz-Masiá, Dolores; Macías-Ceja, Dulce Carolina; Orden, Samuel; Esplugues, Juan Vicente; Calatayud, Sara; Hinojosa, Joaquín; Barrachina, Maria Dolores; Hernández, Carlos (Inflammatory bowel diseases, 2018)
Abstract Background Vitamin D signaling modulates inflammation through the vitamin D receptor (VDR). The synonymous single nucleotide polymorphism (SNP) rs731236, located in the VDR gene, has been associated with a higher risk of Crohn's disease (CD). We analyzed differences in VDR expression levels among CD patients who were homozygous for allelic variants in this SNP and their relevance for disease course. Methods DNA was extracted from blood samples of CD patients, and SNP genotyping was performed by polymerase chain reaction-restriction fragment length polymorphism. Fresh blood from patients was used to isolate peripheral blood mononuclear cells (PBMCs) or to determine the expression of adhesion molecules by flow cytometry. We analyzed the gene expression of VDR and several cytokines in PBMCs using real-time polymerase chain reaction and the protein levels of VDR, NFκB, and IκBα by immunoblot. In addition, we collected complete clinical data for a group of 103 patients, including age at diagnosis, disease location, and disease behavior to compare patient characteristics with respect to genotype. Results We found that CD patients who were homozygous for the risk allele presented lower levels of VDR protein in PBMCs, and that this was associated with an upregulation of IL1β mRNA and activation of lymphocytic adhesion molecules. These patients had a higher risk of developing a B3-penetrating phenotype and of needing to undergo surgery. Conclusion Our data highlight the relevance of vitamin D/VDR signaling in modulating the subjacent inflammation that leads to CD-related complications.